Industrial Relations Climate and Grievance Outcomes - Dastmalchian, Ali; Ng, Ignace (Relations industrielles / Industrial Relations, 1990)
This paper reports the results of a study examining the relationship between the climate of industrial relations and whether grievances are denied, partially granted and fully granted to the grievors. The data used consists of 1115 grievances from six government organizations, and the perceptions of all management personnel of industrial relations climate in these organizations.